Caught in-between: tensions experienced by community mobility scooter users. Issue 10 (21st October 2020) - Jang, Sharon; Mortenson, W. Ben; Hurd, Laura; Kirby, R. Lee
Abstract: The use of mobility scooters is becoming more common due to their effectiveness, social acceptability, and cost. A variety of benefits have been associated with scooter use, including increased mobility, social participation, confidence, and sense of independence; however, scooter users frequently encounter barriers in their communities. This study employed interpretive description to explore the everyday experiences of scooter users as they navigate the social and physical world. Semi-structured interviews were conducted with 20 participants (10 men and 10 women), aged 40 to 86 years. Our analysis identified a single overarching theme, experiencing liminality, which referred to the ambiguous status of mobility scooters and their users. This ambiguity arose from the participants' a) ambulatory status and perceived cognitive capacity ; b) difficulties fitting into the built environment ; and c) experiences of negotiating the social environment . We discuss our findings in light of theorizing about liminality and the social model of disability.